LEARNING SOCIETY ARAB PRA ISLAM (Analisa Historis dan Demografis) - Ahmad Hanif Fahruddin (Kuttab : Jurnal Ilmu Pendidikan Islam, 2017)
The pre-Islamic Arab society is known to be the one upholding the values of racism, feudalism and patriarchy. No doubt if in the time the Arabs were considered as the ignorant society. However, the revolutionary momentum occurred following the emergence of Islam in the desert region. Islam could radically change the Arab social order reaching the point in which human values almost disappeared. This is the beginning of learning society through educational values that are in line with the teachings of Islam. This article tries to unravel how the vertices of education began to disappear in the land of Hijaz. By examining the demographic circumstances of cultures of pre-Islamic Arab society, this article also tries to take the segmentation of society as a basis of analysis of the emergence of the teachings of Islam through the establishment of learning society initiated by Muhammad (PBUH).Keywords: Arab, society, education.